Sensitivity and specificity of thoracic radiography relative to computed tomography in dogs affected by blunt trauma caused by a motor vehicle accident - Le Roux, Christelle (University of Pretoria, 2020)
Dissertation (MMedVet (Diagnostic Imaging))--University of Pretoria, 2019.